EKSISTENSI DIRI WARIA DALAM KEHIDUPAN SOSIAL DI TENGAH MASYARAKAT KOTA (Fenomenologi Tentang Eksistensi Diri Waria Urbanisasi di Kota Malang) - Muhammad Ramadhana Alfaris (Widya Yuridika, 2018)
This research is a purpose to reveal how the self-existence of transvestites urbanization in Malang City. The methods used in this study using the method of transcendental phenomenology because this research is included in the phenomena of social life. Self-existence of transvestites have a broad enough concept in a process which is the soul and the body is formed by imagination, emotion, and cognition. It can be said that a transvestite is the third human figure of absolute gender and the sexuality formed through pressure and socialization, then internalized into action normally, because of the sexuality orientation walks normally in accordance with the gender has been selected. Kata kunci: eksistensi, kehidupan waria, eksistensialisme, fenomenologi